KELAYAKAN BAHAN AJAR CERITA RAKYAT DALAM BUKU TEKS BAHASA INDONESIA SEKOLAH MENENGAH ATAS (Universitas Negeri Semarang, 2022)
The purpose of this reasearch was to describe the feasibility of teaching folklore materials in various Indonesian class X textbooks used by teachers and students in carrying out learning at school. The types of package books are as follows; 1) Indonesian Language Teacher Book for class X of the Ministry of Education and Culture in 2021, the folklore studied is entitled; a.) The Tale of the Noble senses and b) The Tale of Bayan Budiman 2) The Indonesian Language Smart Book for class X Erlangga, the folklore under study is entitled; a) The Tale of Panji Semirang and b) The Tale of Sri Rama and 3) The Book of Indonesian Language and Literature for class X Yrama Widya, the folklore under study entitled; a.) The Tale of Hang Tuah and b) The Tale of Raja Balad. The research method used in this study is the content analysis method, this method is used to reveal further and in-depth information from a text, symbol, image and so on. The saga studied has various advantages and disadvantages in each aspect, of the six saga, which are not suitable for use in teaching materials are the Hikayat Hang Tuah and Raja Balad in the book